Catalytic Hydrodeoxygenation of Fatty Acids for Biodiesel Production - Аntonina A. Stepacheva; Valentin N. Sapunov; Esther M. Sulman M. Sulman; Linda Zh. Nikoshvili; Mikhail G. Sulman; Alexander I. Sidorov; Galina N. Demidenko; Valentina G. G. Matveeva (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
This paper is devoted to the production of second generation biodiesel via catalytic hydrodeoxygenation of fatty acids. Pd/C catalysts with different metal loading were used. The palladium catalysts were characterized using low-temperature nitrogen physisorption and X-ray photoelectron spectroscopy. It was revealed that the most active and selective catalyst was 1%-Pd/C which allowed reaching up 97.5% of selectivity (regarding to n-heptadecane) at 100% conversion of substrate. Moreover, the chosen catalyst is more preferable according to lower metal content that leads the decrease of the process cost. The analysis of the catalysts showed that 1%-Pd/C had the highest specific surface area compared with 5%-Pd/C. Copyright © 2016 BCREC GROUP. All rights reservedReceived: 31st July 2015; Revised: 9th December 2015; Accepted: 30th December 2015How to Cite: Stepacheva, A.A., Sapunov, V.N., Sulman, E.M., Nikoshvili, L.Z., Sulman, M.G., Sidorov, A.I., Demidenko, G.N., Matveeva, V.G. (2016). Catalytic Hydrodeoxygenation of Fatty Acids for Biodiesel Production. Bulletin of Chemical Reaction Engineering & Catalysis, 11 (2): 125-132 (doi:10.9767/bcrec.11.2.538.125-132)Permalink/DOI: http://dx.doi.org/10.9767/bcrec.11.2.538.125-132Article Metrics: (click on the button below to see citations in Scopus)